"I would get real people involved": The perspectives of end users in policymaking - Chervin Lam; Marifran Mattson (Elsevier, 2020)
The implementation of health care services is important for public health. Although the current literature provides much insight into the perspectives of policymakers in charge of such implementations, we know very little about the perspectives of end users. Our study addresses this gap by exploring the perspectives of cancer survivors with regard to the notion of forming a cancer coalition. We found health communication to be highly important and much desired among cancer survivors. Policymakers should include end users in planning and decision-making, and focus on communicating the purposes and benefits of an initiative to end users.